The relationship between atopic dermatitis and atopic itch in children and the psychosocial functioning of their mothers: A cross-sectional study - Kobusiewicz, Aleksandra K.; Tarkowski, Bartlomiej; Kaszuba, Andrzej; Lesiak, Aleksandra; Narbutt, Joanna; Zalewska-Janowska, Anna (Frontiers in Medicine, 2023)
Atopic dermatitis is a chronic inflammatory skin disease significantly affecting patients’ and their parents’ lives. Mothers are mostly responsible for the long-term treatment and their well-being is essential. The major objective of this cross-sectional study was to investigate the relationship between atopic dermatitis in children, especially concomitant itch, and the quality of life, stress, sleep quality, anxiety, and depression of their mothers. The study included 88 mothers of children with atopic dermatitis and 52 mothers of children without atopic dermatitis. All mothers completed sociodemographic questionnaire, the Perceived Stress Scale, the Athens Insomnia Scale and the Hospital Anxiety and Depression Scale. Additionally, mothers of children with atopic dermatitis filled in the Family Dermatology Life Quality Index. The severity of atopic dermatitis and pruritus intensity were evaluated by the Scoring Atopic Dermatitis Index and the Numerical Rating Scale, respectively. The severity of atopic dermatitis and itch significantly correlated with the quality of life, insomnia, and perceived stress of the mothers. Mothers whose children had had atopic dermatitis for more than six months had significantly higher scores of anxiety and depression. The results highlight the importance of screening mothers for functional impairment to provide adequate support. More attention should be directed to the standardization of stepped care interventions addressing factors resulting in the impaired functioning of mothers.